Analisis Perbandingan Fundamental Saham ICBP dan INDF - Vidada, Irwin Ananta; Saridawati, Saridawati; Erica, Denny (JURNAL ADMINISTRASI KANTOR, 2023)
PT Indofood Sukses Makmur Tbk (INDF) and PT Indofood CBP Sukses Makmur Tbk (ICBP) have reported positive performance, with revenue and profit growth in the early part of 2023. Improved financial performance is typically followed by a potential increase in stock prices. INDF is the parent company, while ICBP is its subsidiary. In the stock market, both companies are competing closely to be included in the LQ45 index. Their resilience during the Covid-19 pandemic crisis makes both stocks interesting to watch. To assess their performance, several fundamental analysis indicators are used, including Dividend Yield, Return on Equity (ROE), Price- to - Book Value (PBV), Price - Earnings Ratio (PER), Earnings Per Share (EPS), and Debt - to - Equity Ratio (DER). The fundamental performance of both companies has been tested by their inclusion in the LQ45 index and their ability to navigate the Covid - 19 crisis. Fundamental analysis can be used to predict the future prospects of a company and its impact on future stock prices. Generally, fundamental analysis includes indicators such as Dividend Yield, ROE, PBV, PER, EPS, and DER. Performance data from financial reports and stock prices for the third quarter of 2022 (annualized) were used as reference data, analyzed through the Stockbit application. Comparative research was conducted on fundamental ratios, including the assessment of market valuation in terms of book value and earnings per share. Based on the research conducted on fundamental analysis of financial reports and stock prices for the third quarter of 2022 (annualized), the Consumer Goods sect or listed on the Indonesia Stock Exchange and indexed in the LQ45, it was found that INDF performed better in terms of EPS, PER, PBV, and DY, while ICBP performed better in terms of ROE, and both companies had the same position in terms of DER.       Keywords: Stock Investment, Fundamental Analysis, Financial Performance